A comparison of methods to determine ventilatory efficiency in athletes. - Brown, S. J. (Medicina Sportiva, 2012)
Human ventilatory efficiency is quantified during exercise using the slope of the linear relationship between minute ventilation (¦E) and carbon dioxide output (VCO2), and the oxygen uptake efficiency slope (OUES). However, limited data compare the ventilatory efficiency of trained subjects using different exercise modalities. Methods: In endurance trained males (n = 12, age range 18-25 years), ventilatory efficiency and OUES were quantified during incremental exercise up to maximal oxygen uptake (¦O2max) on (1) a rowing ergometer; (2) a treadmill; (3) a cycle ergometer. Data were compared using a one-way analysis of variance, and where appropriate, a post-hoc t-test. Results: Mean (SD) ventilatory efficiency was 28.41 (3.88), 27.59 (5.09), and 26.72 (6.51), and mean (SD) OUES was 4.96 (0.99), 4.31 (0.94), and 5.39 (1.01) for the rowing ergometer, treadmill, and cycle ergometer, respectively. Mean (SD) ¦O2max was 57.76 (6.39), 55.60 (6.44), and 62.88 (9.06) ml Kg-1 min-1 for the rowing ergometer, treadmill, and cycle ergometer, respectively. A higher ¦O2max and OUES (P < 0.03) were measured during cycle ergometry compared to other modalities. Conclusions: In endurance trained males, measures of ventilatory efficiency appear to be independent of exercise modality, although VO2max and OUES may be higher if cycle ergometry is used.